2013
DOI: 10.1155/2013/152139
|View full text |Cite
|
Sign up to set email alerts
|

Ant-Related Oviposition and Larval Performance in a Myrmecophilous Lycaenid

Abstract: We experimentally assessed ant-related oviposition and larval performance in the Miami blue butterfly (Cyclargus thomasi bethunebakeri). Ant tending had sex-dependent effects on most measures of larval growth: female larvae generally benefitted from increased tending frequency whereas male larvae were usually unaffected. The larger size of female larvae tended by ants resulted in a substantial predicted increase in lifetime egg production. Oviposition by adult females that were tended byC. floridanusants as la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Many lycaenid butterfly species have become myrmecophilous, by which they succeed in gaining fitness. Tending ants not only protect butterfly larvae from enemies, but they also affect larval body size and developmental time [14,15,16,17,18,19,20,21]; the influence of tending ants on the fitness of lycaenids can be substantial, although it varies considerably depending on the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many lycaenid butterfly species have become myrmecophilous, by which they succeed in gaining fitness. Tending ants not only protect butterfly larvae from enemies, but they also affect larval body size and developmental time [14,15,16,17,18,19,20,21]; the influence of tending ants on the fitness of lycaenids can be substantial, although it varies considerably depending on the system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the production of the secretory substances negatively affects both adult mass and developmental time, which may ultimately reduce butterfly fitness [14,15,32]. However, several lycaenid species compensate or overcompensate for the energetic cost of the rewards [17,18,19,20,21,33,34], and such compensation is common in facultatively myrmecophilous lycaenids [18]. Moreover, it has been reported that the influence of tending ants on the body size and developmental time of lycaenids was different between sexes of lycaenids [16,18,19,21] and between tending ant species in facultatively myrmecophilous lycaenids [16,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the behavioural traits of adults, ant-mediated egg-laying has been proposed for many species and experimentally shown for some, including Ogyris amaryllis Hewitson, Jalmenus evora Donovan, and Maculinea teleius (Bergsträsser) (Atsatt, 1981a;Pierce & Elgar, 1985;Van Dyck et al, 2000;Wynhoff et al, 2008), and may even result in oviposition on low-quality plants (Atsatt, 1981b;Rodrigues et al, 2010). Trager et al (2013) consider that understanding how ants are detected by myrmecophilous butterflies as oviposition cues is a priority for future studies on the interaction between these organisms. The use of chemical, tactile, and/or visual cues by butterflies in ant-mediated oviposition has been proposed for different systems, but without the support of experimental evidence .…”
Section: Introductionmentioning
confidence: 99%
“…The use of chemical, tactile, and/or visual cues by butterflies in ant-mediated oviposition has been proposed for different systems, but without the support of experimental evidence . Trager et al (2013) consider that understanding how ants are detected by myrmecophilous butterflies as oviposition cues is a priority for future studies on the interaction between these organisms. Although visual detection of predacious ants has been shown to mediate ovipositing decisions in non-myrmecophilous butterflies that select less risky foliage for larval offspring (Sendoya et al, 2009), the role of vision in oviposition decisions by myrmecophilous butterflies remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some lycaenid species may experience longer or shorter development times and changes in pupal weight due to ant tending intensity and specific species of attendant ant ( Pierce et al 1987 , Robbins 1991 , Wagner 1993 , Fiedler and Samm 1994 , Axén, 2000 , Kaminski and Rodrigues 2011 ). There are specific developmental benefits for some lycaenid butterfly species in which sex-related differences may be observed in either larval growth, pupal weight, or female fecundity depending on ant attendance ( Fiedler and Holldobler 1992 , Cushman et al 1994 , Trager et al 2013 , Mizuno et al 2019 ). Ant attendance can have profound effects on the length of time individuals spend in vulnerable immature stages as well as the resulting fecundity of adults.…”
mentioning
confidence: 99%